2023
DOI: 10.3390/diagnostics13061015
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of the Predictive Value of 18F-FDG PET/CT Metabolic Parameters for PD-L1 Expression in Cervical Cancer

Abstract: Background: Immunotherapy targeting PD-1/PD-L1 has been proven to be effective for cervical cancer treatment. To explore non-invasive examinations for assessing the PD-L1 status in cervical cancer, we performed a retrospective study to investigate the predictive value of 18F-FDG PET/CT. Methods: The correlations between PD-L1 expression, clinicopathological characteristics and 18F-FDG PET/CT metabolic parameters were evaluated in 74 cervical cancer patients. The clinicopathological characteristics included age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Many literatures reported that SUVmax of 18 F-FDG PET/CT could predict PD-L1 expression in lung adenocarcinomas and squamous cell carcinomas ( 25 , 26 ). Meanwhile, SUVmax could predict PD-L1 status in cervical cancer ( 27 ). These all revealed that the tumor lesion FDG activity (glucose activity) was mainly associated with PD-L1 positive expression.…”
Section: Discussionmentioning
confidence: 99%
“…Many literatures reported that SUVmax of 18 F-FDG PET/CT could predict PD-L1 expression in lung adenocarcinomas and squamous cell carcinomas ( 25 , 26 ). Meanwhile, SUVmax could predict PD-L1 status in cervical cancer ( 27 ). These all revealed that the tumor lesion FDG activity (glucose activity) was mainly associated with PD-L1 positive expression.…”
Section: Discussionmentioning
confidence: 99%